Computational Quantum Physics and Chemistry of Nanomaterials - Šob, Mojmír (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue of Nanomaterials collects a series of original research articles providing new insight into the application of computational quantum physics and chemistry in research on nanomaterials. It illustrates the extension and diversity of the field and indicates some future directions. It provides the reader with an overall view of the latest prospects in this fast evolving and cross-disciplinary field